Development and assessment of a two-dimensional role playing computer game on undergraduate students’ intention to use game-based learning tools - Meor Zamari, Wan Nurul Nazirah (2017)
A well-balanced serious game can engage, motivate and even influence learners to continuously use the application for its intended learning purposes. However, bridging both game design and instructional design is not an easy task. Users’ response and perception are crucial to develop serious games that can engage and motivate them. Their acceptance towards the technology proposed plays an important part to determine the game adoption. Game-based learning incorporates game elements such as achievements, levels, points and rewards as means to keep users playing. Thus, this study opts to use game-based learning in the form of serious games to investigate its users’ intention to use the game as an informal medium to practise their values and analytical skills. A 2D role-playing computer game prototype called SightHeart was developed and tested based on instructional design models and game theories. The study used a development methodology and survey as its research design, with descriptive and Pearson correlation for data analysis. Users’ gamification preferences, motivation, engagement, perceived ease of use, perceived usefulness, perceived learning opportunities, attitude and behaviour intention were amongst the variables investigated. A purposive sampling consists of 97 undergraduate students from Universiti Putra Malaysia Serdang were chosen to test SightHeart. Data were collected using survey questionnaire and additional informal interview questions and metrics from the game. A four-point Likert scale was used for items in the questionnaire ranging from (1) “strongly disagree” to (4) “strongly agree”. Results indicated that the game offers high learning opportunities (M=3.18, SD=.539). Respondents also perceived SightHeart to be useful to them (M=3.00, SD=.532) and reported to have positive attitudes towards the game (M=3.04, SD=.595). Consequently, the variables have contributed to high behaviour intention among respondents (M=3.01, SD=.610). In other aspects however, SightHeart scored a fair value on engagement (M=2.88, SD=.577) and motivation (M=2.89, SD=.405). Perceived ease of use was the least scored variable (M=2.86, SD=.505) in the study. Meanwhile Pearson correlation test revealed that there is a positive significant relationship between user motivation [r (97) =0.69**, p = 0.01], engagement [r (97) = 0.47**, p = 0.01], perceived usefulness [r (97) = 0.61**, p =0.01], perceived ease of use [r (97) = 0.25*, p = 0.05], learning opportunities [r (97) = 0.69**, p = 0.01] and attitudes [r (97) = 0.72**, p = 0.01] with their behaviour intention to use SightHeart. An extension to the demographic section to identify respondents’ gamified user types also revealed that majority of them falls under the philanthropist category (M=3.44, SD=.459) based on their motivation in playing and general preferences towards certain game elements. Philanthropist users are known for their tendency to engage in a gameplay that gives sense of purpose and altruism to them (Marczewski et al., 2015). Additionally, qualitative data gained from informal interview serves as credibility assurance to SightHeart’s case study as they validate the quantitative data through triangulation. Ultimately, findings suggested valuable insights for interested designers and scholars in developing serious game applications that are better tailored towards a more effective personalized learning.